Analysis of Anemia Incidence Determinants among Female Students at Islamic Boarding School Al Hidayah 2 Bangkalan - Dini Setiarsih; Rizki Nurmalya Kardina; Andreas Putro Ragil Santoso; Ahmad Miftahul Kaunain; Halimatul Afifah (STIKes Patria Husada Blitar, 2022)
The incidence of anemia is common in adolescent girls. Anemia causes decreased learning achievement due to lack of concentration. This research aimed to analyze the determinant factors associated with the incidence of anemia in female students at Islamic Boarding School Al Hidayah 2 Bangkalan. The research was observational analytic, a cross sectional design. The population was female students at Islamic Boarding School Al Hidayah 2 and the sample size was 72 people. The independent variables include menstrual patterns, sleep patterns, consumption patterns of food sources of iron and nutritional status. The dependent variable was anemia status. Data collection on menstrual patterns and sleep patterns used a questionnaire, consumption patterns with the Food Frequency Questionnaire and anemia status by testing hemoglobin levels. Analysis of the data by Contingency Coefficient test. The results showed that 27.8% of subjects experienced menorrhagia, 54.2% had poor sleep patterns, 58.3% had good food consumption patterns, 25.0% had underweight nutritional status, and 13.9% subjects experienced anemia. Correlation tests showed that the menstrual pattern was significantly related to anemia status (p=0.048). Sleep pattern (p=0.776), food consumption pattern (p=0.908) and nutritional status (p=0.462) were not significantly correlated with the incidence of anemia. Menstrual pattern is the most influential factor of anemia incidence.Â The longer of menstrual period will cause the greater the chance of the subject experiencing anemia.Â